O outeiro rupestre da Botelhinha - Pegarinhos (Alijó) : registo e análise do conjunto de rochas gravadas - Lima, Alexandre (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The text presented here is the monographic study of the carved rocks of Outeiro da Botelhinha, Pegarinhos (Alijó, Trás-os-Montes). At the same time some interpretations are advanced for Outeiro as “a Place” and for the timelines and temporalities of the creation and use of that place during the regional Chalcolithic period (3 mil. BC). However, some of the carved motifs show us that also in later times (Medieval Age, Modern Age...) Outeiro da Botelhinha continued to enjoy great political/symbolic and socio-economic importance in the region of Trás-os-Montes (NW Iberian Peninsula).